2011
DOI: 10.1152/ajpheart.00407.2010
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic dysfunction is associated with cardiac fibrosis in the senescence-accelerated mouse

Abstract: heart failure is a major cause of mortality in the elderly population. It is often preceded by diastolic dysfunction, which is characterized by impaired active relaxation and increased stiffness. We tested the hypothesis that senescence-prone (SAMP8) mice would develop diastolic dysfunction compared with senescence-resistant controls (SAMR1). Pulsed-wave Doppler imaging of the ratio of blood flow velocity through the mitral valve during early (E) vs. late (A) diastole was reduced from 1.3 Ϯ 0.03 in SAMR1 mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 36 publications
3
75
2
Order By: Relevance
“…Further, there is evidence to support accelerated aging in the pathogenesis of COPD and emphysema 49,50 and similar mechanisms have been proposed for diastolic dysfunction. 51,52 In addition, LV myocardial fi brosis has been demonstrated in patients with COPD and cor pulmonale. 53 There are several limitations to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is evidence to support accelerated aging in the pathogenesis of COPD and emphysema 49,50 and similar mechanisms have been proposed for diastolic dysfunction. 51,52 In addition, LV myocardial fi brosis has been demonstrated in patients with COPD and cor pulmonale. 53 There are several limitations to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Mice overexpressing CTGF in a cardiomyocyte-specific manner show accelerated cardiac aging and begin to develop age-related cardiac dysfunction at 7 mo of age (Panek et al 2009). The role of ECM synthesis in cardiac aging is also implicated by the accelerated myocardial fibrosis that accompanies higher TGF-b and CTGF levels in senescence-accelerated mice that display diastolic dysfunction at 6 mo of age (Reed et al 2011). In another study, Bradshaw et al (2010) showed that expression of a matricellular protein, secreted protein acidic and rich in cysteine (SPARC), increased with age, and that deletion of SPARC resulted in reduced fibrillar collagen content in the LV and decreased LV diastolic stiffness.…”
Section: Adverse Extracellular Matrix (Ecm) Remodelingmentioning
confidence: 99%
“…Despite the great difficulty in developing an animal model of DHF age-induced, a recent study has characterized a model demonstrating isolated diastolic dysfunction associated with accelerated aging [235]. This mouse model is a spontaneous senescence model that displays many common geriatric disorders in the human population and recapitulates diastolic dysfunction as it naturally occurs in the elderly.…”
Section: Diastolic Hf Modelsmentioning
confidence: 99%
“…This suggests that the physiologic abnormality manifests over a relatively short period of time and, from an experimental standpoint, adds an advantage as it allows for a more rapid study of pathophysiologic mechanisms. The senescence-accelerated mouse model will probably turn to be a useful model for future studies of age-related diastolic dysfunction, since the better insight into its underlying mechanisms could pave the way for designing specific pharmacologic strategies to prevent or treat this pathology [235].…”
Section: Diastolic Hf Modelsmentioning
confidence: 99%